The languages and peoples of the Müller Mountains; A contribution to the study of the origins of Borneo's nomads and their languages - Sellato, Bernard; Soriente, Antonia (Wacana, Journal of the Humanities of Indonesia, 2015)
The M ller and northern Schwaner mountain ranges are home to a handful of tiny, isolated groups (Aoheng, Hovongan, Kereho, Semukung, Seputan), altogether totaling about 5,000 persons, which are believed to have been forest hunter-gatherers in a distant or recent past. Linguistic data were collected among these groups and other neighbouring groups between 1975 and 2010, leading to the delineation of two distinct clusters of languages of nomadic or formerly nomadic groups, which are called MSP (M ller-Schwaner Punan) and BBL (Bukat-Beketan-Lisum) clusters. These languages also display lexical affinity to the languages of various major Bornean settled farming groups (Kayan, Ot Danum). Following brief regional and particular historical sketches, their phonological systems and some key features are described and compared within the wider local linguistic setting, which is expected to contribute to an elucidation of the ultimate origins of these people and their languages.